Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/nature14426
|View full text |Cite|
|
Sign up to set email alerts
|

Mutant MHC class II epitopes drive therapeutic immune responses to cancer

Abstract: Tumour-specific mutations are ideal targets for cancer immunotherapy as they lack expression in healthy tissues and can potentially be recognized as neo-antigens by the mature T-cell repertoire. Their systematic targeting by vaccine approaches, however, has been hampered by the fact that every patient’s tumour possesses a unique set of mutations (‘the mutanome’) that must first be identified. Recently, we proposed a personalized immunotherapy approach to target the full spectrum of a patient’s individual tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
963
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,052 publications
(1,068 citation statements)
references
References 31 publications
35
963
1
8
Order By: Relevance
“…Neoantigens are tumor specific antigens created by somatic mutations 26 . We found that all AC-NP formulations, with the exception of mPEG AC-NPs, successfully captured neoantigens 24 (Figure 2c, Supplementary Table 1). Notably, AC-NPs also captured a number of damage associated molecular pattern proteins (DAMPs), a broad class of pro-inflammatory molecules that have been shown to potentiate immune response 27 .…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Neoantigens are tumor specific antigens created by somatic mutations 26 . We found that all AC-NP formulations, with the exception of mPEG AC-NPs, successfully captured neoantigens 24 (Figure 2c, Supplementary Table 1). Notably, AC-NPs also captured a number of damage associated molecular pattern proteins (DAMPs), a broad class of pro-inflammatory molecules that have been shown to potentiate immune response 27 .…”
mentioning
confidence: 94%
“…To determine whether AC-NPs captured tumor-specific antigens, we performed an in silico analysis on our mass spectrometry data to determine if any of the captured proteins contain neoantigens expressed by B16F10 cells 24,25 . Neoantigens are tumor specific antigens created by somatic mutations 26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, OVA 257-280 -PC7A NP achieved the maximum therapeutic efficacy, where 50% of animals survived over 40 days. In B16-F10 melanoma, we used a cocktail of either tumor associated antigens (Gp100 21-41, Trp1 214-237, Trp2 173-196 ) or neoantigens (Obsl1 T1764M , Kif18b K739N , Def8 R255G ) 26 in PC7A NP (0.5 μg for each peptide, 30 μg polymer). PC7A vaccination significantly slowed the growth of B16F10 tumors over antigen only, PC7A only and non-treated controls (Fig.…”
mentioning
confidence: 99%
“…Specifically, peptide vaccines derived from MHC class I-restricted tumor antigens offer the promise of inducing robust tumor-specific CD8 + T cell responses 1,2 to promote effective antitumor immunity. 3–6 Unfortunately, the efficacy of class I-restricted peptide vaccines has proven to be limited, 7,8 with overall clinical response rates as low as 3%. 9 Class II CD4 + T cell helper epitopes are also capable of inducing potent antitumor immune responses, 1013 but peptide vaccines consisting of co-administered class I/II epitopes have also not yet experienced widespread clinical success.…”
Section: Introductionmentioning
confidence: 99%